Incorporation of aminoalcohols to tune the properties of polyurethane systems (2024)
It is common practice to incorporate low molecular weight molecules, known as chain extenders, to enhance the performance of polyurethane (PU) material. They usually increase the phase separation between the soft and hard domains, which has a significant impact on the density of hydrogen bonds. Aminoalcohols, molecules with both hydroxyl and amine functional groups, are important building blocks in the synthesis of pharmaceuticals but are also widely used in cosmetics or paints and coatings. Easily derived from abundant natural sources, such as amino acids, aminoalcohols align with the need for renewable and sustainable sources. Despite their importance, the specific reactivity of aminoalcohols towards isocyanates and their contribution to PU-based formulations remain underexplored. They can act as chain extenders as well as crosslinkers and catalysts. This study addressed this knowledge gap by assessing the feasibility of adding various aminoalcohols to create hybrid poly(urethane-urea) formulations. By measuring the exothermicity of the polymerization and gel times, we calculated that all tested aminoalcohols have a catalytic activity on the formation of the polymer network. We also identified DMAMP as a promising reactive catalyst whose integration into the network is of primary interest to formulate products that do not emit volatile organic compounds. Moreover, increasing the amount of aminoalcohols stiffened the foams while maintaining the density constant. X-ray tomography completed the characterizations of the foams. Taken together, these results open possibilities for using aminoalcohols to enhance and tune material performances while contributing to more environmentally friendly PU formulations.